Drought Tolerance Test Of Three Gogo Rice Cultivars Using PEG Atgermination Phase - Mustakim Mustakim; Maemunah Maemunah; Adrianton Adrianton (AGROLAND The Agricultural Sciences Journal (e-Journal), 2017)
Data in 2012 explained that Indonesia had dry land about 148 million ha (78%) and wetland by 40.20 million ha (22%) out of 188.20 million ha of the total land area. The variety of rice which can grow and produce well on marginal land such as gogo rice is very indispensable. This research aimed to find the gogo rice cultivars that can germinate normally in particular osmotic pressure and the tolerance limit on the drought by using PEG 6000 solution. The research was prepared with two-factor factorial design by using Completely Randomized Design. The first factor consisted of three gogo rice cultivars, namely 1. siang, 2. Pulut ko, and 3. roda, while the second factor consisted of four treatments, namely 1. water as control of 2. -1 bar, 3. -2 bar, and 4. -3 bar.Thus, there were 12 combinations of treatment in which each treatment was repeated four times. In the experiment Rolled Paper placed in plastic test method was used in which there were 50 items in each experiment unit.The variable observed was potential for growth, percentage of germination, and germination rate. The research findings reveal that the three cultivars were able to germinate normally only up to -1 bar osmotic pressure, while the pulut cultivar had higher germination capacity compared with siang and roda cultivars up to -3 bar PEG 6000 osmotic pressure. Siang cultivar and -1 bar osmotic pressure gave potential for growth, germination capacity, and germination rate.